Gamification Based Blockchain Tournaments Between Miners - Kenta, Hiroshi; Shino, Yamato; Immaniar, Dewi; Harahap, Eka Purnama; Ahmad, Alfian Dimas Ahsanul Rizki (Aptisi Transactions On Technopreneurship (ATT), 2021)
We have modelled mining resource and cryptocurrency-related relationships into a non-cooperative game. Then we took advantage of the traffic congestion results, set a native convention for the Nash equilibria, and created a short algorithm to find the equilibria. Next, we will make calculations for several system models whose variations follow the existing mining resources and have appropriately allocated according to the details of the mining complexity level that has defeated. In the included resources, the game's result is the allocation of resources as a feature of a normalized Nash equilibrium. In the model that has proposed, we provide a property structure of the type of equilibrium that exists, such as a condition where there are two or more mining infrastructures that will be active and another state that explains that no Miners get results in wanting a specific cryptocurrency, like bitcoin.